Comparative computational analysis of NATO 5.56 mm, APM2 7.62 mm and AK-47 7.82 mm bullet moving at Mach 2.0 in close vicinity to the wall - Salunke, Samruddhi; Shinde, Suryapratap; Gholap, Tanmay; Sahoo, Devabrata (FME transactions, 2023)
Comparative Computational Analysis of NATO 5.56 mm, APM2 7.62 mm and AK-47 7.82 mm Bullet Moving at Mach 2.0 in Close Vicinity to the Wall Various rifles require unique bullets. Each bullet has its capability, speed, and impact on the target. In metropolitan warfare, several bullets are shot close to the solid walls. These near walls affect the pressure distribution over the entire asymmetric bullet. The influence of a reflected shock depends on the angle at which it was reflected and the altitude from the ground to the body of the bullet. The current research emphasizes three bullets of varying diameters used in different types of guns. The first bullet is of NATO 5.56 mm, the second is APM2's 7.62 mm bullet, and the third is a 7.82 mm bullet from an AK-47 rifle. For 2-D steady computations, the supersonic speed of Mach 2 is considered to analyze the flowfield across all three bullets. The heights of the bullet are taken considering the height-to-diameter ratios (h/D ratio) from 0.5 to 3.0. The Mach contour drawn from the numerical simulations is used to analyze the flowfield, and aerodynamic coefficients like lift, drag, and moment are also plotted to analyze the ground effects on the projectile. The comparative analysis showed that the trend of shock wave reflections was similar in the bullets till h/D of 1.5. The APM2 bullet experienced maximum drag, followed by AK-47's 7.82 mm and NATO's 5.56 mm bullet. The 7.82 mm bullet experienced maximum lifting force at h/D = 1.0 due to its larger surface area than the other two ammo. The 7.82 mm bullet experienced a nose-up moment, whereas the other two faced a nose-down moment. As the altitude of the bullets from the ground increased, the ground effect appearing on the bullets reduced. The present comparative analysis research shows that it is suitable to fire an AK-47 bullet from h/D greater than 2.0 and the other two bullets from an altitude greater than or equal to h/D of 3.0.